Intercultural differences in relational strategies at workplace meetings: a case study for two frameworks - Du, Ping (2012)
This study develops and proposes a research approach founded on linking two novel theoretical frameworks for analysing and explaining relational strategies at intercultural workplace meetings, namely, the Multi-Level Model (MLM) and Cultural Self Perception (CSP). The approach is tested through a case study of a problematic meeting in an intercultural workplace in China. At this meeting, the Chinese and western expatriate participants both carefully adopted a range of relational strategies for problem talk. However, the interactions still evolved into a severe confrontation between the Chinese and expatriate participants. The cultural differences in relational strategies are explored on three levels, namely, tum-taking, speech act and situational context. The analysis indicates that while the relational strategies of the expatriate speakers can only be found on the speech act level, those of the Chinese speakers can be found on all of the three levels. Even on the speech act level, there are significant differences between the Chinese and expatriate speakers. It is argued that the communicative breakdown was caused by clashes of expectations of relational strategies for problem talk at meetings, and such differences can be explained by drawing on the framework of CSP. The investigation in this case study thus demonstrates that the combination of the frameworks of MLM and CSP can facilitate both systematic analysis of interactive strategies at different levels and in-depth understanding of the cultural roots for the choices of relational strategies at intercultural workplace meetings.